Adaptation in practice: lessons from teenage pregnancy programmes in Sierra Leone - Castillejo, Clare; Buell, Stephanie (ODI, 2020)
A discussion of initial learning emerging from the SLRC ’Adaptive approaches to reducing teenage pregnancy in Sierra Leone’ action research project.

Mainsreaming gender in an adaptive, politically smart governance programme - Lessons from Institutions for Inclusive Development in Tanzania - Laws, Ed (ODI, 2020)
• This paper looks at the experience of gender mainstreaming in the Institutions for Inclusive Development (I4ID) programme – an adaptive, politically smart governance programme in Tanzania. • When development programmes try to engage with political stakeholders and align with the priorities of wider coalitions there is a danger that gender equality is de-prioritised. • It is important that formal political economy analysis, as well as other data collection, analysis and consultation exercises, are gender-sensitive. Teams should also look for ways to make gendered political and power analysis part of the everyday routine practice of staff. • Working politically and adaptively to advance gender objectives calls for staff with a specific skillset, as well as links to appropriate networks and political stakeholders. It also implies establishing checks and incentives to hold staff and partners accountable for gender objectives, and strong and consistent messaging from team leaders.

Rethinking value for money for adaptive, politically smart programmes - Lessons from Institutions for Inclusive Development in Tanzania - Laws, Ed (ODI, 2020)
- This short paper draws out lessons for working effectively with and through partners, based on the experience of the Institutions for Inclusive Development (I4ID) programme – an adaptive, politically smart governance programme in Tanzania. • Cultivating effective partnerships can be a key part of delivering locally legitimate projects that have the potential to create sustainable change. Adaptive and politically informed ways of working create specific opportunities and challenges for doing this well. • Flexible and adaptive programmes are deliberately designed to experiment and to make small investments in different areas, to see what will work. While this is often important for making headway on complex challenges, it can also leave partners exposed and can undermine trust. • It can also be challenging to balance the need to meet accountability commitments to donors while allowing local partners to take the lead in pursuing their own objectives. • Co-creating plans, priorities and activities with partners has the potential to resolve some of these tensions. But the time and patience required to do this successfully should not be underestimated, and can be difficult to maintain in the face of pressure from donors to see results within a confined timeframe.

Examining the results and adaptation ideas in foreign aid - Janus, Heiner (University of Manchester, 2020)
This thesis applies ideational and institutional theories to analyse how two specific ideas, results and adaptation, have changed the theory and practice of development cooperation. The thesis addresses the question of why the results and adaptation ideas are often treated as binaries and how this debate has evolved historically. In a first theoretical paper, the evolution of results and adaptation is conceptualised as a combination of institutional layering and diffusion within development organisations. The second theoretical paper applies ideational theory, in particular, the coalition magnet framework, to China as a donor country. The empirical papers apply ideational and institutional theories to study aid projects funded by the World Bank and China in the Rwandan agriculture sector. The third paper analyses through which mechanism, results-based principal-agent relationships or problem-driven iterative adaptation, the World Bankâs Program for Results in the agriculture sector in Rwanda has led to increased agricultural productivity. The paper combines causal process tracing and contribution analysis to investigate two underlying theories of change of the Program for Results. The fourth paper applies the same framework and methodology to the Chinese Agricultural Technology Demonstration Center in Rwanda. The fifth paper compares both projects, the World Bank project and the Chinese project. The thesis finds that the ideas of results and adaptation are often presented as mutually exclusive mainly at the general level of public philosophies or paradigms, but show overlap and potential for integration on the level of framing policy problems and policy solutions. The thesis also demonstrates that there is unexplored potential for convergence between China and Development Assistance Committee donors around âcoalition magnetâ ideas. The empirical part of the thesis reveals how results-based and adaptive causal mechanisms co-exist within given aid interventions by the World Bank and China, how these interact and how they ultimately contribute to achieving development outcomes. The key finding is that the broader political context of the Rwandan agricultural sector is the main factor for determining development outcomes, which neither the World Bank project nor the Chinese projects take into account. The comparison of the World Bankâs and Chinaâs interventions finds that donor organisations need to address how results-based ideas in combination adaptive development ideas can be better tailored to fit into the specific context of the Rwandan agriculture sector.

Working effectively through partnerships - Lessons from Institutions for Inclusive Development in Tanzania - Laws, Ed (ODI, 2020)
• This paper looks critically at the approach to value for money (VfM) in the Institutions for Inclusive Development (I4ID) programme – an adaptive, politically smart governance programme in Tanzania. • Adaptive, politically smart programmes like I4ID aim to deliver VfM by learning about what will work in complex environments, and quickly incorporating those lessons into delivery. When functioning properly, they can rapidly wind down activities as new information emerges and divert funding to more effective alternatives. • This means that adaptive programmes will achieve their potential to deliver strong VfM when their processes are good – when appraisal of experimental efforts is timely, consistent, knowledgeable and politically astute. As these programmes mature in their implementation phase, VfM evaluation should be focused on checking for a culture of adaptation and learning supported by strong adaptive processes. • While economy is important for adaptive programmes, it is also important that keeping costs low does not deprive teams of the resources, staff, and management and administration time they need to gather information, experiment, learn and adapt.

Nuru Kenya transition from Nuru International, Kenya - Dillan, Haley; Ouma, Joel; Yamron, David (What Transformation Takes - Evidence of Responsible INGO Transitions to Locally Led Development Around the World, 2020)
This case study is an example of a phased transfer of ownership and responsibility from INGO Nuru International to Nuru Kenya, including the exit of all international staff. Post-transition, Nuru Kenya is managed entirely by Kenyan staff, although it continues to receive financial support from Nuru International. A lot of the elements described are aligned with Adaptive Management ways of working.